PGPR Bacillus subtilis for multifaceted benefits in vegetables - Loganathan, M.; Rai, A. B.; Pandey, K. K.; Nagendran, K.; Tripathi, A. N.; Singh, B. (Indian Horticulture, 2019)
The potential plant growth-promoting rhizobacteria (PGPR), Bacillus subtilis (isolate Bs2) from chilli rhizosphere based on their plant growth-promotion and plant disease control profile were identified. Talc based formulation of Bacillus subtilis (Bs2) showed promising results against Fusarium wilt and Pythium and Rhizoctonia damping off in tomato, including Colletotrichum leaf spot and Sclerotium collar rot of cowpea. The Bs2 treatment leads to increase in lycopene content of tomato by 102.44% over untreated control and improves keeping quality/shelf-life of fruits by 15 days.